Placental Growth Factor Regulates the Pentose Phosphate Pathway and Antioxidant Defense Systems in Human Retinal Endothelial Cells - Saddala, Madhu Sudhana (J Proteomics, 2020)
The molecular mechanisms whereby placental growth factor (PlGF) mediates its effects in nonproliferative diabetic retinopathy (DR) are unknown. To better understand the role of PlGF in DR, we used tandem mass tags (TMT)-labeled quantitative proteomics to human retinal endothelial cells (HRECs), treated anti-PlGF antibody, and PBS as a control. Functional annotation and pathway enrichments were performed, which suggested that the differentially expressed proteins (DEPs) were involved in key metabolic processes, protein binding, and membrane, pentose phosphate pathway PPP and adherens junction. We conducted integrated gene profiles of our previously published transcriptomic data to the TMT-labeled proteomics data. The results showed the sixty proteins were found to be changed at the mRNA levels. The functional annotation conducted for the sixty proteins suggested that 58.3% of proteins were involved in PPP, 25% of proteins were in interleukin-12 singling and 16.7% of proteins were involved in glycolysis and gluconeogenesis pathway. Mass spec results were validated by transendothelial electrical resistance measurement by an electrical cell-impedance sensing and western blot analysis of VE-cadherin, G6PD. These findings suggest that the PPP proteins and antioxidants may act as a downstream target of PlGF and may play a decisive role in HREC biological functions in DR.